A multicenter, retrospective archive study of radiological and clinical features of ALK-positive non-small cell lung cancer patients and crizotinib efficacy - YUMUK, PERRAN FULDEN (My University, 2024)
To evaluate radiological and clinical features in metastatic anaplastic lymphoma kinase+ non-small cell lung cancer patients and crizotinib efficacy in different lines. This national, non-interventional, multicenter, retrospective archive screening study evaluated demographic, clinical, and radiological imaging features, and treatment approaches in patients treated between 2013-2017. Totally 367 patients (54.8% males, median age at diagnosis 54 years) were included. Of them, 45.4% were smokers, and 8.7% had a family history of lung cancer. On radiological findings, 55.9% of the tumors were located peripherally, 7.7% of the patients had cavitary lesions, and 42.9% presented with pleural effusion. Pleural effusion was higher in nonsmokers than in smokers (37.3% vs. 25.3%, P = .018). About 47.4% of cases developed distant metastases during treatment, most frequently to the brain (26.2%). Chemotherapy was the first line treatment in 55.0%. Objective response rate was 61.9% (complete response: 7.6%; partial response: 54.2%). The highest complete and partial response rates were observed in patients who received crizotinib as the 2nd line treatment. The median progression-free survival was 14 months (standard error: 1.4, 95% confidence interval: 11.2-16.8 months). Crizotinib treatment lines yielded similar progression-free survival (P = .078). The most frequent treatment-related adverse event was fatigue (14.7%). Adrenal gland metastasis was significantly higher in males and smokers, and pleural involvement and effusion were significantly higher in nonsmokers - a novel finding that has not been reported previously. The radiological and histological characteristics were consistent with the literature data, but several differences in clinical characteristics might be related to population characteristics.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine